(untitled) (Journal of Global Accounting, 2023)
This study examine tax multiplicity on earnings and investment decisions of small and Medium Enterprises in Nigeria. Guided by three research questions and hypotheses, descriptive survey design was used. The population of the study consists of 3144 registered SMEs in South Eastern Nigeria while 336 registered SMEs were sampled as determined using simple random sampling method. Primary data were collected using structured questionnaire and analysed using simple percentage, Z-test and Pearson Product Moment correlation with the aid of Statistical package for social science version 20. The findings revealed that tax multiplicity has significant negative effect on earnings and investment decisions of small and medium scale enterprise and that there is significant relationship between excess tax charges and survival of small and medium scale enterprises. The researcher concluded that tax multiplicity has significant negative effect on growth of small and medium scale enterprises. The researcher recommends that Government should create simple, favourable policy covering only the operators of SMEs, considering the volatility of their businesses as well as unifying the various taxes into one. Owners of SMEs should enlighten themselves appropriately on the form of business they want to embark upon before venturing into it to make them better equipped by going for entrepreneurial training programs this will go a long way to reduce the early folding up of SMEs in Nigeria. There is also a great need for the government to put the size and age of SMEs into consideration in tax levying as well as employ tax holiday as a major tax incentives for newly established small and medium enterprises because it stimulates their investing power thereby exempting them from other tax liabilities.